PENERAPAN GILAS (TEKNOLOGI PENGOLAHAN SUSU) KAMBING DI DESA GUNUNG BATIN UDIK KECAMATAN TERUSAN NUNYAI KABUPATEN LAMPUNG TENGAH PROPINSI LAMPUNG - Iswanto, Darmawan; Maulana, M. Irsyan; Hidayah, Taufik; Martalena, Cyntia; Kurniawan, Rangga (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
So far, we know the different types of milk usually consumed some of them milk cows, goats and horses. But most of us only consume cows milk because it tastes sweet and a good source of vitamins and minerals contained in it are very high. But cows milk that we consume every day that even though there are other content contained therein, but not much more with other milk that goats milk has more health benefits compared to cows milk can help prevent anemia (iron deficiency) and prevent removal of minerals on softening of bone or bone (demineralization) osteoporosis. In this regard, efforts to provide information and the application of technology acquired in the lecture bench with goat milk processing technology implementation. This extension activities carried out in the village of Gunung Batin Udik Terusan Nunyai District, Central Lampung Lampung Province. Farmers especially inner village Gunung Batin Udik Terusan Nunyai District Central Lampung not know how goat milk processing that adds value to the nutrition and income of farmers in the village of Gunung Batin Udik Terusan Nunyai District in particular and in general. Implementation of the activities carried out by way of: delivery of material on the use of goats milk, how and materials to be used in the processing of goat milk, practicing how to manufacture dairy goats with a pasteurized goats milk, goats milk yogurt, and provide time for discussion and consultation with farmers.